Analisis Organoleptik (Aroma dan Warna) dan Nilai TBA dalam Pendugaan Umur Simpan Bumbu Mi Aceh dengan Metode Accelarated Shelf-Life Testing (ASLT) Menggunakan Persamaan Arrhenius - Muhammad Nazly Hasibuan; Eti Indarti; Novia Mehra Erfiza (Jurnal Teknologi dan Industri Pertanian Indonesia, 2019)
Aceh noodle seasoning was made from red chili, red onion, garlic, cardamom, turmeric, ginger, cumin, candlenut, coriander and pepper. All ingredients were mashed and then sauteed in a frying pan with the addition of cooking oil. In the food industry it is necessary to determine the shelf life so the consumers know the quality of the product. Shelf life is the periode of a product from the production process until the product has decreased in quality or is not suitable to consumption. This research was conducted using a semi-empirical accelerated shelf-life testing method with the Arrhenius equation. The estimation of shelf life was determined through the quality change of Aceh noodle seasoning which packed with aluminum foil packaging and stored based on temperature factor (room temperature, 40o C, and 50o C). Each sample was analyzed of thiobarbituric acid test, flavour and descriptif test in duplicate. The results show that Aceh noodle seasoning shelf life based on the critical parameters  stored at room temperature (27-30oC) was 71 days, at 40oC was 49 days, and at 50oC was 35 days.